DURABILITY AND MECHANICAL PROPERTIES OF HYBRID CONCRETE BLENDED WITH GROUND GRANULATED BLAST FURNACE SLAG, METAKAOLIN, AND SILICA FUME - Mardenov, Madiyar (School of Engineering and Digital Sciences, 2023)
This paper evaluates the characteristics of ordinary portland cement (OPC) and blended concrete (BC) with 20% ground granulated blast furnace slag (GGBFS), as well as mixtures with 5, 10, and 15% metakaolin (MK) and silica fume (SF) replacement from the total weight of the BC. Eight mixtures were designed to be analyzed, that are: 100% OPC, 100% BC, BC with 5%, 10%, and 15% substitution by MK and SF. The experimental program includes air content, slump, hardened density & voids, density & compressive strength, and non-steady-state migration & rapid chloride permeability of concrete mixtures. The finding suggested that mixtures with partial MK replacement need more air-entraining and superplasticizer admixtures with an increasing replacement level to match the target range. As for mixtures with SF, it is necessary to evaluate the air-entraining and superplasticizer admixtures and their role in the casting and curing processes, as well as additional tests on the quality and replacement amount. The MK content significantly increases density and decreases % voids in comparison with control mixtures, but in the case of SF, it behaves in contrast. Because of that, the compressive strength results were affected by a directly proportional relationship between % of void, the density, and the compressive strength in the mixtures. All that demonstrated that mixtures with MK notably increased the compressive strength and density of mixtures, but not in the SF case. Overall, the chloride permeability, sulfate attack, and freeze and thaw results were enhanced by the MK and SF as replacement content increased. The research’s findings indicate that the implementation of MK and SF as partial BC replacement materials in concrete provides visible durability, mechanical and hardening properties. Therefore, mixtures with these materials are applicable in Kazakhstani severe weather and environmental conditions.
Keywords: type of access: open access; ordinary portland cement; blended concrete; metakaolin; silica fume